Assessment of Physicochemical Properties of Water Samples - Priyanshi; Phiri, Tiwine Alice; Prachi; Chhaya; Tomar, Somya; Sagar, Sushant; Awasthi, Adamya; Sharma, Shashank (Journal for Research in Applied Sciences and Biotechnology, 2023)
Water is life and abundant on earth but is not safe for human consumption due to anthropogenic activities and puts people at risk of developing waterborne diseases. There are physical and chemical parameters of water that must be checked regularly and compared to the guidelines provided to determine whether it is safe for human consumption. In the current study, water samples were collected from different locations at Sharda University, Greater Noida, and standard tests were carried out to analyze their physicochemical parameters, including temperature, odour, taste, colour, pH, total dissolved solids, electrical conductivity, turbidity, hardness, alkalinity, and chloride content to assess the quality of the water. Our results demonstrated that drinking water collected from different sites was more suitable for human consumption than groundwater.